2021
DOI: 10.1002/bbb.2206
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the anthropogenic effect of biomass energy utilization and economic sustainability on environmental degradation in E7 economies

Abstract: Inspired by the Sustainable Development Goals (SDGs), this study focuses on the need for responsible and clean energy consumption, climate change mitigation, and sustainable economic growth. To this end, the study investigates the connection between biomass energy consumption, real GDP, investment in the energy sector, and CO2 emissions in the emerging (E7) countries – China, India, Brazil, Mexico, the Russian Federation, Indonesia and Turkey – for the period 2000–2018. The study uses a battery of techniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(33 citation statements)
references
References 48 publications
(92 reference statements)
4
29
0
Order By: Relevance
“…Gyamfi et al [ 34 ] employed the FMOLS and DOLS estimators to explore the relationship between CO 2 emissions and GDP in 7 emerging economies and established that GDP increases environmental degradation. Adebayo & Akinsola [ 35 ] investigated the causal connection between CO 2 emissions and GDP for the case of Thailand from 1971 to 2018.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gyamfi et al [ 34 ] employed the FMOLS and DOLS estimators to explore the relationship between CO 2 emissions and GDP in 7 emerging economies and established that GDP increases environmental degradation. Adebayo & Akinsola [ 35 ] investigated the causal connection between CO 2 emissions and GDP for the case of Thailand from 1971 to 2018.…”
Section: Literature Reviewmentioning
confidence: 99%
“…PEC is the ability of firms to produce and consume environment friendly energy in manufacturing and production activities, while PECP is the quantitative value or measure of environment friendly energy performance defined by consumption per unit time, consumption per unit production, or characteristics specific to production. Logically, green energy consumption can mitigate the level of carbon emissions (Gyamfi et al [30]). Past research showed that EMS is a determinant for PEC and carbon reduction and business performance (Fernando and Hor [26]; González-Benito and González-Benito [28]; Şenol [58]).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…The overall discussion comes to the following four policy outcomes, i.e. : Environmental sustainability is imperative for achieving healthcare sustainability and green growth agenda (see, Koondhar et al 2021 ; Ahmad et al 2021 ; Gyamfi et al 2021 ). An efficient use of natural resources and reducing resource wastes helpful for improving the livelihood of the low-income strata group (Salahuddin et al 2020 ; Imran et al 2021 ; Goswami and Nautiyal 2020 ).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Environmental sustainability is imperative for achieving healthcare sustainability and green growth agenda (see, Koondhar et al 2021 ; Ahmad et al 2021 ; Gyamfi et al 2021 ).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%